The Analisis Ekuitas Merek Dan Komunikasi Pemasaran Terpadu Terhadap Keputusan Pembelian Smartphone Samsung - Febriyan Subagya; Asep Muhamad Ramdan; R Deni Muhammad Danial (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The research was aimed at describing brand equity, integrated marketing communications and purchase decisions. The research was also conducted to analyze the influence of brand equity and integrated marketing communications towards purchase decisions for Samsung smartphones in Sukabumi. The methods applied in the research were descriptive and associative research methods with quantitative approach. Moreover, by using non-probability sampling method with purposive sampling technique, questionnaires were distributed to 398 respondents who were Samsung smartphone users in Sukabumi city. The techniques of analyzing data used by the researcher were multiple linear regression, determination coefficient, and hypothesis testing. The results of the research show that the correlation coefficient analysis is amounted to R-0.777 which has a strong interpretation. Subsequently, the determination coefficients of brand equity and integrated marketing communications toward purchase decisions is aggregated to 60.3%, while the rest of 39.7% is influenced by other factors not included in the research. The result of the simultaneous test (F-Test) indicate that brand equity and integrated marketing communication influence purchase decisions altogether. Moreover, the result of the partial test (t-test) obtain the value of sig. < 0.050 so it states that there is a significant and positive influence between brand equity toward purchase decisions and there is an influence from integrated marketing communication towards purchase decisions. Keywords: Brand Equity, Integrated Marketing Communication, Purchase Decision.